SEJARAH PERKEMBANGAN DESA LIHUNU KECAMATAN LIKUPANG TIMUR KABUPATEN MINAHASA UTARA TAHUN 1925-2013 - BOYANGAN, SILVANA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This writing takes topic about the Silvan formative history LihunuLikupang's district Regency East Minahasa Is Year North 1925 2013. The explanation of this topic, the writer not only issued what happened in the year 1925, but also explain about the period before. In this writing writer utilizes to methodic consisting of history four phases, which is: Heuristic, Critical analysis, Interpretation, and last phase is Historiography. Besides utilize history method, in this case writer also utilize social's knowledge as tool helps to enable analyses and interpretation is sharper to answer what does become problem in a writing. Lihunu's village constitute village that its resident comes from Sangihe's tribe, On year 1900 get in three brotherses of Sangihe's Islands means their arrival be subject to be catch fishes at Lihunu'sSilvan waters. since first few input and makes a abode it Sangihe's society is gone upon on its happening density, looking for new region, looking for new employment, etcetera. They work as fisherman and farmer then experiencing a lot of good developing in economic area, pendidkan, governance, and tradition. Kata Kunci : Sejarah, Perkembangan Desa, Pembangunan Desa, Perubahan Sosial.